Activation of β-Catenin Signaling in Androgen Receptor–Negative Prostate Cancer Cells - Xinhai Wan; Jie Liu; Jing-Fang Lu; Vassiliki Tzelepi; Jun Yang; Michael W. Starbuck; Lixia Diao; Jing Wang; Eleni Efstathiou; Elba S. Vázquez; Patricia Troncoso; Sankar N. Maity; et al. (2012)
Abstract Purpose: To study Wnt/β-catenin in castrate-resistant prostate cancer (CRPC) and understand its function independently of the β-catenin–androgen receptor (AR) interaction. Experimental Design: We carried out β-catenin immunocytochemical analysis, evaluated TOP-flash reporter activity (a reporter of β-catenin–mediated transcription), and sequenced the β-catenin gene in MDA prostate cancer 118a, MDA prostate cancer 118b, MDA prostate cancer 2b, and PC-3 prostate cancer cells. We knocked down β-catenin in AR-negative MDA prostate cancer 118b cells and carried out comparative gene-array analysis. We also immunohistochemically analyzed β-catenin and AR in 27 bone metastases of human CRPCs. Results: β-Catenin nuclear accumulation and TOP-flash reporter activity were high in MDA prostate cancer 118b but not in MDA prostate cancer 2b or PC-3 cells. MDA prostate cancer 118a and MDA prostate cancer 118b cells carry a mutated β-catenin at codon 32 (D32G). Ten genes were expressed differently (false discovery rate, 0.05) in MDA prostate cancer 118b cells with downregulated β-catenin. One such gene, hyaluronan synthase 2 (HAS2), synthesizes hyaluronan, a core component of the extracellular matrix. We confirmed HAS2 upregulation in PC-3 cells transfected with D32G-mutant β-catenin. Finally, we found nuclear localization of β-catenin in 10 of 27 human tissue specimens; this localization was inversely associated with AR expression (P = 0.056, Fisher's exact test), suggesting that reduced AR expression enables Wnt/β-catenin signaling. Conclusion: We identified a previously unknown downstream target of β-catenin, HAS2, in prostate cancer, and found that high β-catenin nuclear localization and low or no AR expression may define a subpopulation of men with bone metastatic prostate cancer. These findings may guide physicians in managing these patients. Clin Cancer Res; 18(3); 726–36. ©2011 AACR.